2014
DOI: 10.1785/0120140035
|View full text |Cite
|
Sign up to set email alerts
|

Regional Earthquake Likelihood Models II: Information Gains of Multiplicative Hybrids

Abstract: The Regional Earthquake Likelihood Models experiment in California tested the performance of earthquake likelihood models over a five-year period. First-order analysis showed a smoothed-seismicity model by Helmstetter et al. (2007) to be the best model. We construct optimal multiplicative hybrids involving the best individual model as a baseline and one or more conjugate models. Conjugate models are transformed using an order-preserving function. Two parameters for each conjugate model and an overall normalizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 33 publications
1
32
1
Order By: Relevance
“…As mentioned, the model that specifies the longterm rate of smaller earthquakes in UCERF3-ETAS has demonstrated skill in the formal prospective tests conducted by the Collaboratory for the Study of Earthquake Predictability (CSEP, Helmstetter et al, 2007;Zechar et al, 2013;Helmstetter and Werner, 2014;Rhoades et al, 2014). However, we had to change these rates near several faults (via the ApplyGridSeisCorr parameter; Fig.…”
Section: Scientific Implicationsmentioning
confidence: 99%
“…As mentioned, the model that specifies the longterm rate of smaller earthquakes in UCERF3-ETAS has demonstrated skill in the formal prospective tests conducted by the Collaboratory for the Study of Earthquake Predictability (CSEP, Helmstetter et al, 2007;Zechar et al, 2013;Helmstetter and Werner, 2014;Rhoades et al, 2014). However, we had to change these rates near several faults (via the ApplyGridSeisCorr parameter; Fig.…”
Section: Scientific Implicationsmentioning
confidence: 99%
“…The sample fθ z i ; ω i g can either stem from one or more logic trees or from a collection of models (hereafter, the term "model" means either an independent model or a final branch of a logic tree); the only requirement is that fθ z i ; ω i g represents an unbiased sample of the epistemic uncertainty. The models' output may be correlated, and the weight attached to each model should properly take into account not only the confidence on each model (based on expert opinion and/or on quantitative evaluation of the forecasting performances), but also the possible strong correlation with other models (Marzocchi et al, 2012;Rhoades et al, 2014).…”
Section: Ensemble Modelingmentioning
confidence: 99%
“…In addition to the forecasting from each magnitude frequency model, we also examine the performance of an ensemble forecasting that combines the two forecasts from these models. Ensemble forecasting has been implemented in some studies for probabilistic earthquake forecasting [e.g., Gerstenberger et al, ; Marzocchi et al, ; Helmstetter and Werner, ; Rhoades et al, ]. Akaike [] suggested that natural weighting of each forecast is proportional to the factor exp[ln L ( X learn ) − p ], where L ( X learn ) and p are the likelihood function and the number of model parameters, respectively.…”
Section: Statistical Models For Underlying Aftershock Activitymentioning
confidence: 99%